Taxonomic study of Wild Species of the Brassicaceae Family in Diyala Province-Iraq - Hashim, Nisreen Sabbar; Dawood, Wisam Malik; Al-Shahwany, Ayyad Wajih (Journal of agricultural, environmental and veterinary sciences, 2023)
The research dealt with study one of the aspects of biodiversity in Diyala province, where the study included comperhenation Survey of all wild plant species of the Brassicaceae family present in the province during the years 2021-2022. the research was based on 48 plant samples with their duplicates collected by the researcher.where 24 species belonging to 16 genera of the Brassicaceae family, their classification was scientifically classified, and common names in Iraq and Arab world and their permanence, economic, medical, toxic, industrial forage or used as fuel and other uses.with mentioning their geographicl distribution in the provinces of Iraq and their affiliation in neighboring countries (Turkey, Syria, Saudi, Arabia, Jordan, Kuwait and Iran), Due to the convergence of systems and natural climatic conditions, especially between Iran and the study area.it was found from the results of the study that all the collected species are herbaceous plant, as 18 species were annuals, and 4 types were permanence variety (annuals or biannuals or perennials), and 1 types were perenials .In terms of economic importance most of them 16 types are nutritional and medicinal uses for humans, and 10 types pastoral and moderately palatable fodder, and 5 types of them are poisonous, and perhaps the most toxic of them is in the flowering period dueto drug intervention, tow are decorations plants, 8 types are Aromatic plants with distinctive aromatic scen, the Mustard spicies (Sinapis sp) rich in minerals and organic matter are used as green manures to improve soil quality, some of them have an allelopathic effect, as their roots secrete substancesthat prevent the growth of other plants nearby, as in Capsella bursa-pastoris and Lepidium aucheri, and the spicies Raphanus raphanistrum it makes anatural herbicide, and plant Sisymbrium irio Which is a plant an aggressive nature that strongly competes with local plants and was classified as an invasive plant in some countries (Australia &Hawaii), the most species are widespread in the other Iraqi provinces in terms of geographical affiliation in neighboring countries, The highest percentage of geographical affiliation to these reached in Iran then Syria, Turkey, Jordan, Saudi Arabia and Kuwait.